PENINGKATAN PENJUALAN PADA SHOWROOM JEPANG MOTOR GIANYAR MELALUI PELATIHAN GOOGLE ADS DAN META ADS: TRAINING AND GUIDANCE ON USING ADS AT SHOWROOM JEPANG MOTOR GIANYAR - M. Azman Maricar; Rifky Lana Rahardian; Made Doddy Adi Pranatha; Tegar Andhika Nugraha; Lulut Aji Aditya (LPPM Universitas Abdurrab, 2025)
Jepang Motor Gianyar Showroom, a used motorcycle dealership, faces stagnant sales despite utilizing social media for marketing. A primary reason for this stagnation is the underutilization of digital advertising platforms like Google Ads and Meta Ads due to a lack of understanding regarding their implementation. This community service initiative aimed to enhance the showroom's capabilities in digital marketing, specifically through the effective use of Google Ads and Meta Ads. The provided solution encompassed a two-day program involving training and hands-on assistance, covering introduction, practical application, and evaluation of both advertising platforms. The two-day activity included pre-tests and post-tests to measure partner understanding, utilizing 10 statements with a 5-point Likert scale ranging from